THE IMPLEMENTATION OF RAFT (ROLE, AUDIENCE, FORMAT, TOPIC) STRATEGY IN TEACHING WRITING TO INCREASE THE STUDENTS’ WRITING SKILL AT THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 NGADILUWIH - Kulsum, Umi; Putri, Kristanti Yuntoro (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 9 No 2 (2019): LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
The aim of this study was to knowthe implementation of RAFT (Role, Audience, Format, Topic) to increase students’ writing skill at eleventh grade of SMA Negeri 1 Ngadiluwih Kediri. The qualitative approach was used to design this research. The instruments were observation guide, interview guide, questionnaires and documentation. The subject of this research was the eleventh grades students of XI.IPA1 at SMA Negeri 1 NGadiluwih. The result of several instruments are (1) observation, the resultof implementation RAFT strategy in teaching writing was very good because the real implementation same as theori RAFT, (2) interview guide, the background of RAFT strategy can improve students writing skill in learning writing but in the RAFT strategy, there is problem that students often got that problem. That problem was about the format of text, (3) questionnaire in this research was good response because the students’ responses for about up to 75% like the learning writing by using RAFT strategy, (4) documentation, the students’ score was very good and the lesson plan was good because the lesson plan can manage class to be better. From the results, it is recommended that the teacher should held RAFT strategy in teaching writing to increase students writing value.